Biological characteristics and genome analysis of a novel phage vB_KpnP_IME279 infecting Klebsiella pneumoniae - Zhang, Rongrong; Zhao, Feiyang; Wang, Jiuru; Pei, Guangqian; Fan, Hang; Zhangxiang, Lilan; Mi, Zhiqiang; Shi, Taoxing; Liu, Hui; Tong, Yigang (Folia microbiologica, 2020)
Klebsiella pneumoniae (family Enterobacteriaceae) is a gram-negative bacterium that has strong pathogenicity to humans and can cause sepsis, pneumonia, and urinary tract infection. In recent years, the unreasonable use of antibacterial drugs has led to an increase in drug-resistant strains of K. pneumoniae, a serious threat to public health. Bacteriophages, viruses that infect bacteria, are ubiquitous in the natural environment. They are considered to be the most promising substitute for antibiotics because of their high specificity, high efficiency, high safety, low cost, and short development cycle. In this study, a novel phage designated vB_KpnP_IME279 was successfully isolated from hospital sewage using a multidrug-resistant strain of K. pneumoniae as an indicator. A one-step growth curve showed that vB_KpnP_IME279 has a burst size of 140 plaque-forming units/cell and a latent period of 20 min at its optimal multiplicity of infection (MOI = 0.1). Phage vB_KpnP_IME279 survives in a wide pH range between 3 and 11 and is stable at temperatures ranging from 40 to 60 °C. Ten of the 20 strains of K. pneumoniae including the host bacteria were lysed by the phage vB_KpnP_IME279, and the multilocus sequence typing and wzi typing of the 10 strains were ST11, ST37, ST375, wzi209, wzi52, and wzi72, respectively. The genome of vB_KpnP_IME279 is 42,518 bp long with a G + C content of 59.3%. Electron microscopic observation showed that the phage belongs to the family Podoviridae. BLASTN alignment showed that the genome of the phage has low similarity with currently known phages. The evolutionary relationship between phage vB_KpnP_IME279 and other Podoviridae was analyzed using a phylogenetic tree based on sequences of phage major capsid protein and indicates that the phage vB_KpnP_IME279 belongs to the Podoviridae subfamily. These data enhance understanding of K. pneumoniae phages and will help in development of treatments for multidrug-resistant bacteria using phages.
Keywords: zastoupení bazí; sekvenování celého genomu; Hospitals; Drug Resistance, Multiple, Bacterial; Multilocus Sequence Typing; Temperature; fylogeneze; Genome, Viral; techniky typizace bakterií; mnohočetná bakteriální léková rezistence; bakteriofágy; RNA, Ribosomal, 16S; Phylogeny; antibakteriální látky; Klebsiella pneumoniae; hostitelská specificita; lidé; Anti-Bacterial Agents; Humans; Base Composition; mikrobiologické techniky; multilokusová sekvenční typizace; RNA ribozomální 16S; odpadní vody; Bacterial Typing Techniques; genom virový; Podoviridae; teplota; Microbiological Techniques; Sewage; nemocnice; Bacteriophages; Host Specificity; Whole Genome Sequencing